IMPLEMENTATION OF CRM METHODS TO IMPROVE SALES QUALITY OF BUNUT SEBRANG UMI CLOTHING SHOP - Windi Safitri; Guntur Maha Putra; Febby Madonna Yuma (Kresnamedia Publisher, 2022)
Along with the times, the business world is experiencing rapid development, especially in the business world, such as selling fashion products. Therefore, a good strategy is needed. In maintaining more advanced competitiveness, companies must develop information technology. Another thing that must be considered in making our business more advanced is the relationship with customers, which is also an important thing to always maintain, to manage good relationships with new customers or regular customers by using the Customer Relationship Management (CRM) method. The Customer Relationship Management (CRM) method can make it easier for Umi Clothing Store owners to retain existing customers and make it easier for shop owners to get new customers. The research method used in this research is qualitative research. This research will only utilize data obtained from the research location and input it without changing anything.